Welche Überzeugungen haben Lehramtsstudierende zur Geschichte der Mathematik? : Ergebnisse der Studie ÜberLeGMa (mathematica didactica, 2019)
The study ÜberLeGMa examined the beliefs of 141 mathematics pre-service teachers on the structure of mathematics, the history of mathematics, and the teaching and learning of the history of mathematics. The paper presents the key findings of the study, including statements on the structure and distribution of these beliefs and their relationships. The aim of the paper is to provide empirical foundations for studying the impact of higher education learning opportunities in this area and to formulate recommendations for incorporating appropriate learning arrangements into teacher education.